Security Aspects in an Intelligent Lighting System for Public Squares using Fog Computing - Bezerra, Wesley R.; Souza, Cristiano A.; Westphall, Carla M.; Westphall, Carlos B. (Anais do Workshop de Computação Urbana (CoUrb); 2025: Anais do IX Workshop de Computação Urbana, 2025)
Security in public spaces is a fundamental factor for citizens and can be provided by digital tools such as remote sensing. However, the security of such tools is also an important issue, and violating this security can lead to the susceptibility of loss of security in public spaces. This work presents a use case where an authentication solution is applied to ensure security in a smart lighting system in public squares. The use case, the adversary and its motivation, the threat modeling of the system, and a general discussion about this study are presented. As a result, a threat model with countermeasures is presented, and security aspects brought about by the use of the adopted multi-factor authentication mechanism with reputation are discussed.